2016
DOI: 10.1016/j.otsr.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

EOS-based cup navigation: Randomised controlled trial in 78 total hip arthroplasties

Abstract: II, randomised controlled trial with limited statistical power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…These findings are consistent with two other studies, 44,45 though they could not be included in our pooled analysis because risk estimates for dislocation risk were not available. Though computer-assisted surgical techniques improve cup position in THR surgery 46 and are increasingly being adopted by surgeons, 47 little evidence exists to show they actually improve outcomes and reduce complication rates in total joint replacement. 44,45,48,49 In the United States, it has been estimated that there will be an increase in the demand of primary THRs by 174% between 2005 and 2030.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with two other studies, 44,45 though they could not be included in our pooled analysis because risk estimates for dislocation risk were not available. Though computer-assisted surgical techniques improve cup position in THR surgery 46 and are increasingly being adopted by surgeons, 47 little evidence exists to show they actually improve outcomes and reduce complication rates in total joint replacement. 44,45,48,49 In the United States, it has been estimated that there will be an increase in the demand of primary THRs by 174% between 2005 and 2030.…”
Section: Resultsmentioning
confidence: 99%
“…The natural acetabular orientation in arthritic hips is quite variable and knowledge of this using navigation provides a better understanding of this orientation in individual patients [ 36 ], which offers an advantage for precise positioning of the acetabular component. Several studies have demonstrated convincingly that the acetabular orientation is more precise with navigated THA [ 37 , 38 ], acetabular component was beyond the Lewinnek’s safe zone only in 8.63% of hips in the navigated group, compared with 28.4% in the conventional group [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…We reviewed the clinical use of hip surgery navigation systems from 2008 to the present, for a total of 13 navigation systems, including commercial navigation systems and navigation systems independently developed by medical institutions, of which there were seven image‐free navigation systems. Stryker Navigation (Stryker Corp, Kalamazoo, Michigan) 12,141‐146 appeared seven times, Orthopilot Navigation System (B/Braun‐Aesculap, Melsungen, Germany) 7,147‐150 appeared five times, Vector Vision hip CT‐based ver. 3.5.2 (BrainLab, Heimstetten, Germany) 14,151‐153 appeared four times, Navitrack imageless computer navigation system (ORTHOsoft, Montreal, Canada) 154‐156 appeared three times, BrainLab hip 6.0 (BrainLab, Heimstetten, Germany) 157,158 appeared twice, and the N‐navi (TEIJIN NAKASHIMA MEDICAL, Okayama, Japan), 159 BrainLab hip 2.1‐5.1 (BrainLab, Heimstetten, Germany), 160 MAKO robot arm navigation (Stryker Corp, Kalamazoo, Michigan), 161 Ci System (Orthopaedics, Inc, Warsaw, Indiana, and BrainLAB AG, Feldkirchen, Germany), 13 Orthosoft Hip 2.2 Universal Surgical Technique (Zimmer, Warsaw, Indiana), 162 AchieveCAS (Smith & Nephew, Inc), 163 VVHIP3.5 (BrainLAB, Feldkirchen, Germany), 164 and Hip unlimited 5.0 (BrainLab, Heimstetten, Germany) 165 each appeared once.…”
Section: Computer‐assisted Orthopaedic Surgery Navigation Systemsmentioning
confidence: 99%
“…With the development of computer technology, the emergence of some new registration methods has shortened the operation time and improved the placement and positioning accuracy 160 . In a survey study, 148 the proportion of cups in the safe zone was 67% in patients who used surgery navigation systems, whereas in patients who underwent traditional surgery, the proportion of cups in the safe zone was 38%. Compared to freehand positioning, the application of surgery navigation systems significantly reduces the risk of cup positioning outside the safe zone.…”
Section: Computer‐assisted Orthopaedic Surgery Navigation Systemsmentioning
confidence: 99%